The Return of South American Travestis/Trans to Their Societies of Origin: Between Acceptance, Tolerance and Rejection - Pérez Ripossio, Ramiro (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
The article analyzes the experiences of temporary return of South American travestis/trans to their societies of origin after having completed migration in the Metropolitan Area of Buenos Aires. These people migrate as a consequence of the hostilities they experience in their surroundings and with the expectations of accessing rights in the AMBA. Once the migration is completed, the South American transvestites/trans communicate with their families and try to rebuild the bonds through experiences of return in which they can perceive acceptance, tolerance or rejection. The methodological approach of the article is qualitative and 44 in-depth interviews were conducted through theoretical sampling. It was found that migration, in some cases, enables greater social acceptance in the societies of origin. This is because displacement allows them to conquer and expand capitals that are perceived by families and environments as indicators of migratory success.